2005
DOI: 10.1002/j.1556-6678.2005.tb00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Managed Mental Health Care: Intentional Misdiagnosis of Mental Disorders

Abstract: Managed health care regulations affect the manner in which counselors provide and deliver services. Counselors are challenged by ethical and legal dilemmas when diagnostic codes in the Diagnostic and Statistical Manual of Mental Disorders (American Psychiatric Association, 2000) are not honored for insurance reimbursement. In this article, the authors examine violations of codes of ethics and legal statutes and the consequences related to intentional misdiagnosis of mental disorders for reimbursement. They exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…There is much written about similar issues in other countries, including the impact of managed care, the role of insurance companies which only pay for treatment following DSM medical diagnosis (e.g., AFTA, ; Braun & Cox, ; Cushman & Gilford, ; Moses, ; Wylie, ) and the linking of diagnoses to eligibility for disability payments and/or school support funding (e.g., Angell, ).…”
Section: An Outline Of Controversies Relating To Dsm‐5mentioning
confidence: 99%
See 1 more Smart Citation
“…There is much written about similar issues in other countries, including the impact of managed care, the role of insurance companies which only pay for treatment following DSM medical diagnosis (e.g., AFTA, ; Braun & Cox, ; Cushman & Gilford, ; Moses, ; Wylie, ) and the linking of diagnoses to eligibility for disability payments and/or school support funding (e.g., Angell, ).…”
Section: An Outline Of Controversies Relating To Dsm‐5mentioning
confidence: 99%
“…For example, if a biomedical/diagnostic paradigm is seen as being incompatible with a practitioner's preferred frame, the practitioner may feel forced to utilise the former approach for funding or other purposes, despite the lack of fit with his/her own ideology and whilst continuing to use another frame in clinical work. This raises ethical issues, particularly where funding depends on diagnosis and practitioners could be accused of fraudulent practice (Braun & Cox, ; Crews & Hill, ; Denton, ; Moses, ). Furthermore, there may be concern that the use of incompatible frames may be counterproductive or unhelpful for the client.…”
Section: An Outline Of Controversies Relating To Dsm‐5mentioning
confidence: 99%
“…A diagnosis allows for reimbursement by third-party payers (i.e., health insurance companies or agency grant funders; Braun & Cox, 2005). Insurance companies require a medical diagnosis for reimbursements.…”
Section: Informed Consent Considerations and Diagnosismentioning
confidence: 99%
“…Clients who are not aware that not all DSM diagnoses are reimbursable may agree to incur the risks of receiving a diagnosis but not receive the financial benefit (Braun & Cox, 2005). Although the Paul Wellstone and Pete Domenici Mental Health Parity and Addiction Equity Act of 2008 (the Federal Mental Health Parity Act; U.S. Department of Health and Human Services, 2008) prohibits providing discrepant benefits for mental health and substance abuse treatment, thirdparty payers are not required to reimburse for mental disorders that are not biologically based (U.S. Department of Health and Human Services, 2008).…”
Section: Informed Consent Considerations and Diagnosismentioning
confidence: 99%
“…In other words, counselors may be tempted to "upcode" (Cooper & Gottlieb, 2000, p. 199), giving an acute problem a more severe diagnosis than presenting symptoms warrant for a presenting problem, or to "downcode" (p. 199) to an Axis I diagnosis when the client presents with just an unreimbursable diagnosis (e.g., an Axis II diagnosis; APA, 2000). In the process, such counselors misrepresent their work to third parties (Braun & Cox, 2005;Danzinger & Welfel, 2001;Kanapaux, 2003). Danzinger and Welfel (2001) found that 44% of counselors responding to a survey "indicated that they had changed or would change a client's diagnosis in order to receive additional managed care reimbursement" (p. 146).…”
Section: Accuracy Versus Misrepresentationmentioning
confidence: 99%